Acoustic features of emotional expression in 5-year-old children with autism spectrum disorder - Okuizumi, Daichi; Terada, Kazunori; Ishii, Azusa; Ohmoto, Yoshimasa; Shimizu, Hitomi; Imamura, Akira; Iwanaga, Ryoichiro; Kumazaki, Hirokazu (Frontiers in Psychiatry, 2025)
BackgroundChildren with autism spectrum disorders (ASD) exhibit poor prosodic performance, which is associated with their poor language and social skills. Prosody serves important communicative functions not only at grammatical and pragmatic levels but also at the emotional level. This study investigates the acoustic features of emotional expression in children with ASD compared to typically developing (TD) children, within a narrowly defined age cohort restricted to 5-year-old participants.MethodsNineteen children with ASD and 19 TD children, aged 5 years, participated in this study. We investigated the differences in the fundamental frequency (f0) ranges in three emotional expression settings (i.e., neutral, liking, and disliking).ResultsThe f0 range in the neutral setting was greater in children with ASD than in TD children (p = 0.04). There were no significant differences in the f0 range between the three settings in the ASD group (p = 0.61). There were significant differences between the neutral and liking settings (p < 0.01) and the liking and disliking settings (p < 0.01) in the TD group. In the ASD group, a negative correlation was observed between the f0 range in the liking setting and the Social Responsiveness Scale, Second Edition T-score (p < 0.01).DiscussionBy focusing on the relationship between acoustic features and emotional expression setting and by restricting the age of participants, our results demonstrate the trend of acoustic features in children with ASD. To deepen the understanding of the relationship between f0 and emotion, future studies investigating prosody in a range of emotional expression settings are needed.